2017
DOI: 10.3892/etm.2017.4429
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the angiotensin II-p22phox-reactive oxygen species signaling pathway, apoptosis and 8-oxoguanine-DNA glycosylase 1 retrieval in hyperoxia-induced lung injury and fibrosis in rats

Abstract: The present study was designed to explore the impact of hyperoxia on lung injury and fibrosis via the angiotensin II (AngII)-p22phox-reactive oxygen species (ROS) signaling pathway, apoptosis and 8-oxoguanine-DNA glycosylase 1 (OGG1) repair enzyme. Newborn Sprague-Dawley rats were randomly divided in the newborn air group, newborn hyperoxia group and newborn intervention group, the latter of which was administered the chymotrypsin inhibitor, 2-(5-formylamino-6-oxo-2-phenyl-1, 6-dihydropyrimidine-1-yl)-N-[4-dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…By acting on AT1 receptors ( Kummer et al, 2008 ), Angiotensin II (Ang II), indeed, induces free radical generation, activates dendritic cells, stimulates synthesis and release of proinflammatory and chemoattractant cytokines, promotes the expression of endothelial adhesion molecules and leukocyte margination and migration in tissues ( Benigni et al, 2010 ). Similar effects have been demonstrated also in the lung where Ang II promotes free oxygen radical formation ( Wang et al, 2017 ), enhances vascular permeability and edema formation ( Zhang and Sun, 2005 ), and contributes to tissue damage and remodeling by promoting the apoptosis of alveolar epithelial cells ( Wang et al, 1999 ) and the proliferation of fibroblasts ( Marshall et al, 2000 ). Ang II proinflammatory effects are homeostatically counteracted by another RAS peptide, Angiotensin (1-7) [Ang-(1-7)] that is generated by the alternative metabolism of Ang I or Ang II by ACE2 ( Silva and Teixeira, 2016 ), an 805 amino acids transmembrane metallopeptidase, cloned 20 years ago by Tipnis et al (2000) .…”
Section: The Ras System In Pulmonary Inflammationsupporting
confidence: 57%
“…By acting on AT1 receptors ( Kummer et al, 2008 ), Angiotensin II (Ang II), indeed, induces free radical generation, activates dendritic cells, stimulates synthesis and release of proinflammatory and chemoattractant cytokines, promotes the expression of endothelial adhesion molecules and leukocyte margination and migration in tissues ( Benigni et al, 2010 ). Similar effects have been demonstrated also in the lung where Ang II promotes free oxygen radical formation ( Wang et al, 2017 ), enhances vascular permeability and edema formation ( Zhang and Sun, 2005 ), and contributes to tissue damage and remodeling by promoting the apoptosis of alveolar epithelial cells ( Wang et al, 1999 ) and the proliferation of fibroblasts ( Marshall et al, 2000 ). Ang II proinflammatory effects are homeostatically counteracted by another RAS peptide, Angiotensin (1-7) [Ang-(1-7)] that is generated by the alternative metabolism of Ang I or Ang II by ACE2 ( Silva and Teixeira, 2016 ), an 805 amino acids transmembrane metallopeptidase, cloned 20 years ago by Tipnis et al (2000) .…”
Section: The Ras System In Pulmonary Inflammationsupporting
confidence: 57%
“…Furthermore, study has confirmed that angiotensin II-induced senescence of HVECs senescence and gene expression of p16 INK4a [51], angiotensin II-mediated production of vascular superoxide anion could contribute to endothelial dysfunction, hypertension, and atherosclerosis. A NAD(P)H oxidase has been found to be a major endothelial source of superoxide anions [52], angiotensin II upregulated the transcription of NAD(P)H oxidase p22phox, which increased the production of O 2− [53], which in turn, might be one of the main contributors to HVECs senescence.…”
Section: Angiotensin IImentioning
confidence: 99%
“…For example, Ang-II induces dose-dependent apoptosis in human and rat alveolar epithelial cells (AECs) through its interaction with AT1R [37][38][39][40]. A number of different signaling pathways are involved in the induction of apoptosis in AECs by Ang-II/AT1R [41,42]. Wang and colleagues found that activation of pro-oxidant signals and superoxide production by Ang-II/AT1R pathway contributed to hyperoxiainduced lung injury and fibrosis [41].…”
Section: Downstream Effects Of the Ace/ang-ii/at1r Axis In Vili And Ardsmentioning
confidence: 99%
“…A number of different signaling pathways are involved in the induction of apoptosis in AECs by Ang-II/AT1R [41,42]. Wang and colleagues found that activation of pro-oxidant signals and superoxide production by Ang-II/AT1R pathway contributed to hyperoxiainduced lung injury and fibrosis [41]. Li and colleagues found that Ang-II/AT1R pathway caused activation of NF-κB and JAK2/STATs pathways, and induced apoptosis in AECs in response to seawater inhalation-induced lung injury [42].…”
Section: Downstream Effects Of the Ace/ang-ii/at1r Axis In Vili And Ardsmentioning
confidence: 99%